(untitled) (NAU Journal of Technology and Vocational Education, 2024)
Adoption of innovative pedagogical practicesto improve students’ learning and academic performance has remained a crucial factor in educational programmes. The study ascertained the perception of accounting students on the adoption of self-evaluation learning strategies for enhanced academic performance in colleges of education in South East Nigeria. The design of the study was a descriptive survey conducted with 520final year accounting studentin colleges of education in South East Nigeria. A sample size of 226 (77 males and 149 females) was drawn for the study using Taro Yamane formula. One research question guided the study and one null hypothesis was tested at 0.05 level of significance. A validated structured questionnaire was used for data collection. Cronbach alpha method was used to establish the internal consistency of the instrument. Data collected were analyzed using arithmetic mean and t-test statistic. The findings of the study revealed that students agreedthey adopt eight out of the nine listed selfevaluation learning strategies for enhancing their academic performance in financial accounting.They disagreed that they prepare a short quiz at the end of each financial accounting lecture to evaluate their understanding of the course content. Gender did not significantly influence respondents’ mean ratings of self-evaluation learning strategies they adopt for enhanced academic performance in financial accounting. Based on the findings, the researchers recommended among others that accounting educators should emphasize the teaching of all the self-evaluation learning strategies such as students assessing themselves at the end of each accounting lecture to evaluate their understanding of the course content, to improve their academic performance in financial accounting.